2017
DOI: 10.3382/ps/pew219
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of dietary lipids and vitamin E level on performance, blood eicosanoids, and response to mitogen stimulation in broiler chickens of different ages

Abstract: The effects of the dietary polyunsaturated fatty acids (PUFA) n-6:n-3 ratio and vitamin E (vE) on the levels of pro-inflammatory eicosanoids, the incorporation of docosahexaenoic acid (DHA) and arachidonic acid (AA) into immune tissues, and changes in leukocyte population after phytohemagglutinin (PHA) challenge were investigated in broiler chickens of different ages. One-day-old female broilers (48 per treatment) were fed 4 different wheat-soybean-corn-based diets containing corn oil with a high PUFA n-6:n-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…The liver product of α-tocopherol oxidation (α-tocopheryl quinone) was eventually excreted in the bile, thus the hyperactivity of hepatocytes could have led to liver enlargement. Similarly, it was documented in our previous study (Konieczka et al., 2017a ) that feeding diets with the increased vE level (300 mg kg –1 ) over a period of 42 d caused the enlargement of the bursa, suggesting a pro-oxidative activity of high vE doses in broilers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The liver product of α-tocopherol oxidation (α-tocopheryl quinone) was eventually excreted in the bile, thus the hyperactivity of hepatocytes could have led to liver enlargement. Similarly, it was documented in our previous study (Konieczka et al., 2017a ) that feeding diets with the increased vE level (300 mg kg –1 ) over a period of 42 d caused the enlargement of the bursa, suggesting a pro-oxidative activity of high vE doses in broilers.…”
Section: Discussionsupporting
confidence: 86%
“…Studies on beneficial activities of n-3 long-chain polyunsaturated fatty acids ( LC-PUFA ) in key biological processes have been conducted for at least 3 decades. A simple dietary intervention with PUFA n-3 may affect chicken immunity (Swiatkiewicz et al., 2015 ; Konieczka et al., 2017a ), and enriches poultry products with these fatty acids ( FA ) to the level providing health benefits for humans (Givens, 2015 ; Konieczka et al., 2017b , c ). Therefore, studies in broiler chickens have been mostly focused on the functional impact of different LC-PUFA sources and their dietary level on lipid metabolism in birds.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of strategies have been investigated towards anti-inflammatory effect. Our previous work [16] showed that although feeding broilers diets high in n-3 fatty acids (FAs) and with an increased vE dose clearly limited the availability of AA and consequently antagonised lipid peroxidation during mitogen stimulation. This study provides evidence that the specific response in challenge conditions in birds is mediated by the simultaneous action of different enzymes, which produce lipid hormones involved in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Different fatty acids have differential health effects on chickens. Consumption of unsaturated fatty acids (in particular n‐3 PUFA) has been associated with some beneficial health effects to chickens . However, there is a need for caution to be taken when using fats rich in MUFA and PUFA as they are more susceptible to oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of unsaturated fatty acids (in particular n-3 PUFA) has been associated with some beneficial health effects to chickens. [23,24] However, there is a need for caution to be taken when using fats rich in MUFA and PUFA as they are more susceptible to oxidation. Thereby, there is the risk of the broilers being exposed to oxidative products which can adversely affect their health and productivity, as well as the sensory quality and shelf-life of their products.…”
Section: Introductionmentioning
confidence: 99%